(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Background: Hemoglobin E beta thalassaemia is common hemolytic anemia in South-East Asia. Though Bangladesh is situated in a Thalassaemia prone region but there is no published data regarding spectrum of disease pattern of Hemoglobinopathies. This study done to see the prevalence of b Thalassaemia and other haemoglobinopathies in patient attended the Chattagram Maa-Shishu O General Hospital. Methods: This is a retrospective descriptive study that was carried out in Chattagram Maa Shishu-O-General Hospital. Patient with Thalassaemia and other Hemoglobinopathies (n=290) of different ages attended the Thalassaemia ward during the period from 2011 July to 2013 June were enrolled as study subject. Detailed history and hemoglobin electrophoresis result were obtained from patient register book. Analysis was done with the help of Statistical Package for Social Science (SPSS Version 12.0) software package. Results: It was observed that the onset of Haemoglobinopathies was significantly high from infant to childhood period (1-10 yr) with a percentage of 53% (p<0.05). Male and female difference was found statistically insignificant (p>0.05). The prevalence of HBE b Thalassaemia patients was found highest in percentage (40.34%). Conclusion: Hb E b-Thalassaemia was the most common variety among all types of Hemoglobinopathies. Chatt Maa Shi Hosp Med Coll J; Vol.17 (2); Jul 2018; Page 50-52